Methodical concept of training loads optimisation in sprint contest - Gabrys, T. (5th World Congress of Performance Analysis of Sport, 2001)
The approximation, with the use of the least quadrants method, was utilised to describe the correlation between the improvement of sports results and the volume of training loads in the various areas of energetic processes. It was assumed that there is a close correlation between training loads in various areas of energetic processes at each stage of training course. The above assumption was used to establish the basis of algorithm and allowed to calculate approximation of sports result, according to the volume of training load, which was described by linear or quadratic equation. The following equation was used: R = ao + i,j=14 aijNi Nj, , in which R - result improvement, Ni - volume of training load in selected area of energetic processes (i=1 aerobic, i=2 aerobic-anaerobic, i=3 anaerobic-glycolytic, i=4 anaerobic-alactic) ao and aij - index of approximation. The description of optimal structure of training load required the calculation of extreme value with the use of the equation system: / Nk ( aijNiNj) = 0; N0=0; k=1,2,3,4. Calculation of 15 independent indexes of quadratic equation was needed for four types of training load. To obtain the objective data the linear equation was used for further calculations: R = a0 + 4i=1 ai Ni, in which ao and ai were the partial indexes of linear regression, and this regression was used to assess the contribution of examined parameter to total improvement of a given criteria. According to the hypothesis there is a specific interrelation between values of training loads volume in various areas of energetic processes and thanks to this, the achievement of maximum value of improvement of selected criteria is possible. Therefore the experimental data maybe calculated with the use of correlation of parabolic character described by the following equation expressing the extreme value R = a0 + a1N1 + a2N2i. The results of calculations for the group of high class sprinters (100 - 200 m), which were performed according to the above concept, are presented in a table.